Teacher Strategies for Instilling Character Education in 21st Century Learning in Elementary Schools - Riyadi, Diki; Giwangsa, Sendi Fauzi (International Conference on Elementary Education, 2025)
Twenty-first-century learning requires teachers not only to develop students’ cognitive competencies but also to cultivate character values as the foundation for shaping a moral, adaptive, and competitive generation. This study aims to describe elementary school teachers’ strategies in instilling character values within 21st-century learning. The research employed a descriptive qualitative methodwith data collected through in-depth interviews with elementary school teachers. The findings show that teachers implemented various integrative and contextual strategies, such as role modeling, projectbased learning, the integration of character values into all subjects, and the reinforcement of positive cultural habits in the school environment. The character values developed include religiosity, discipline, responsibility, honesty, cooperation, creativity, independence, environmental awareness, patriotism, andtolerance. Teachers designed learning activities by preparing lesson plans or teaching modules that contain character values, linking them to the Pancasila Student Profile, and applying authentic assessments. Technology was also utilized through educational videos, animations, and characterbased educational games. The study also identified several challenges, including the negative influenceof social media, limited parental supervision, teachers’ administrative workload, and difficulties in measuring character development. Overall, instilling character education in the digital era requires innovative and collaborative strategies, technological support, and continuous enhancement of teacher competencies.